Liturgy against apostasy: Marian commemoration and the Jews in Visigothic Iberia. - Ihnat, Kati (Early Medieval Europe, 2017)
One of the most remarkable features of the earliest surviving liturgy for a feast of the Virgin Mary from seventh-century Iberia is its incorporation of polemical material directed against Jews. This polemical dimension is explored here in the context of contemporary theological polemics and Visigothic law, particularly in relation to attempts to baptize Jews by force. Evidence that ecclesiastical leaders opposed the policy but had to come up with strategies to prevent those baptized from apostatizing raises the possibility that the Marian liturgy was intended to communicate Christian doctrine and warn against Jewish error among recent converts, as well as to assert episcopal control over Christian identity in the Visigothic kingdom.